A Legal Analysis of Judges' Legal Considerations in State Administrative Disputes Relating to the Cancellation of Building use Rights Certificates - Riska Ayu Khusnul Laila; Siti Marwiyah; Sri Sukmana Damayanti (Fox Justi : Jurnal Ilmu Hukum, 2026)
Overlapping land rights disputes between historical evidence claims and modern administrative registration trigger complex legal uncertainty in Indonesia. This study aims to analyze the implementation of the rechtmatigheid principle by the Supreme Court in Decision Number 281 K/TUN/2023 regarding the cancellation of Building Use Rights Certificates based on Article 30 paragraph (1) letter c of PP No. 24 of 1997, as well as to dissect the judge's considerations in rejecting the Judicial Review in Decision Number 124 PK/TUN/2024. The research method used is normative legal research with a statute approach and a case approach. The results of the study indicate that the Supreme Court prioritizes the value of procedural legal certainty (Rechtssicherheit) over the material claims of individuals who neglect to use the 90-day deadline for filing a lawsuit after a deadlocked mediation, in line with the doctrine of vigilantibus non dormientibus iura subveniunt. The definitive rejection of the application for Judicial Review is based on the failure to fulfill the criteria of decisive novum (new, decisive evidence) as regulated in a restrictive manner in SEMA Number 2 of 2019. The conclusion of the study confirms that the validity of certificates in the land administration system is highly dependent on the integration between compliance with official procedures and the vigilance of legal subjects in defending their rights.